The Revisionary Normativity of Constructive Empiricism - Bujokas, Justas; Šaulauskas, Marius Povilas (Problemos, 2014)
What is the nature and epistemic status of contemporary scientific knowledge? And, more generally, how is rational cognition possible at all? In the contemporary philosophy of science these questions are primarily tackled in the debates between empiricism and scientific realism. It seems that Bas van Fraassen’s constructive empiricism (CE) serves as the most important version of the longstanding British empirical tradition nowadays. The paper both draws on and contributes to the critical points of the argumentation of van Fraassen, Gideon Rosen and Marc Alspector-Kelly by offering a new version of normative interpretation of CE. It is argued that epistemological normativity is implicated in all versions of CE and should be understood not only as inevitable but also heuristically useful. Inevitable, because the fact/value dichotomy is not absolute as it follows from the critical evaluation of the basic arguments under consideration in terms of irreducible ambiguity of CE and of the methodological premises this ambiguity implies. Heuristically useful, because the implied flexible normativity of CE, in comparison with rigid ontological postulates of scientific realism, offers epistemologically more modest and descriptively more copious conception of science encompassing the vast multitude of ever-changing epistemic, normative and axiological practices. And, at the end of the day, the heuristic potential of CE is warranted by the moderate agneological revision of modern knowledge that CE, being an outspoken version of modern philosophy of science, cannot but engage with.